Evaluation of three instructional methods of teaching for undergraduate medical students, at King Saud university, Saudi Arabia - Eiad A Al-Faris; Hamza M Abdulghani; Khalid A.B. Abdulrahman; Norah A Al-Rowais; Abdulaziz A.B. Saeed; Shaffi A Shaikh (Wolters Kluwer Medknow Publications, 2008)
Background: There is an international move from traditional curriculum towards the learner - centered, and patient-oriented curriculum. In spite of its advantages, problem-based learning requires a larger number of teaching staff and space. This study was done to compare the problem-based learning (PBL), lectures and modified PBL methods. Methods: Thirty-three fifth year medical students who were taking the Family Medicine rotation participated in the study at the College of Medicine, King Saud University. Three instructors participated in the teaching of three topics to the three groups of students. Students acted as control for themselves across the three instructional methods, namely; lectures, PBL and modified PBL. The main outcomes were students' recall of knowledge, problem solving skills and topic comprehension. Results: In the initial assessment, there was a significant difference in favor of PBL and the modified PBL regarding comprehension of the topic as tested by the short answer questions (p = 0.0001), problem solving skills as tested by the modified essay question (p = 0.002). Non- significant results were observed at the second stage of assessment. The modified PBL method was the preferred one for 39% of the students, followed by the PBL (36%) and lastly the lectures (25%). Conclusion: This empirical study suggests some advantages for the PBL method and the modified PBL over the lecture method. Larger studies are needed to confirm our results of this important issue as the modified PBL is an affordable option for schools that can not meet the staff and space requirements of the PBL curriculum.